Read it yourself ; Emergency Rescue Level 2 - Ladybird (Bharat Ladybird, 2016)
Who comes to help us in an emergency? Read about the men and women who rescue people in trouble. For more than 35 years, the bestselling Read it yourself with Ladybird has helped children learn to read. All books feature essential key words. Title-specific words are repeated to practice throughout. Designed to be read independently at home or used in a guided reading session at school. All titles include comprehension puzzles, guidance notes, and book band information for schools. This Level 2 title is ideal for children who have received some initial reading instruction and can read short, simple sentences with help.
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction